(untitled) (Annual Transactions of the Nordic Rheology Society, 2024)
Understanding the tribological behavior of blood-lubricated interfaces is considered relevant for the design of heart pumps, heart valves or for the understanding of the blood flow in very narrow blood vessels. Tribological studies with real biological materials are challenging, e.g., due to their limited stability or potential risk of infections. To overcome these challenges, artificial materials are used in this study to mimic real blood and the biological interfaces. As for the lubricant, a hydrogel-based artificial blood with a glycerol-water solution, as a continuous phase, is used. Various compositions of artificial blood are investigated and compared with real plasma as well as platelet-rich plasma as lubricants. Soft biological interfaces are represented by a glass-ball-on-three-elastomeric pins setup. Results from tribological model system measurements on the different lubricants are shown in the form of Stribeck curves and possible lubricating mechanisms are discussed. Results from complementary shear rheological measurements of the blood fluids are shown and discussed.